Changing Strategies and Mixed Agendas: Contradiction and Fragmentation within China's External Propaganda - Wang, Clyde Yicheng (The Journal of contemporary China, 2023)
China's external propaganda, or waixuan, is organized by two separate bureaucratic systems - the 'propaganda system' and the 'foreign affairs system.' This article examines waixuan's changing strategies and the bureaucratic structure's adjustments. It argues that since 2012, waixuan has moved on from its previous emphasis on traditional culture in the Jiang and Hu periods to promoting China's development model. The Foreign Ministry bears the pressure to project the image of a great power, making waixuan increasingly ideology-oriented and inflexible. Meanwhile, the great power narrative provides both opportunities and pressure for the propaganda system to use waixuan to feed nationalism among domestic audiences, even though it has been cautious about nationalist mobilization. Such nationalism, in turn, further ideologizes waixuan, making it difficult to attract foreign audiences.